Maria Zambrano: scrittura di sé come confessione, tra esilio e storia - Giosi, Marco (Studi sulla Formazione/Open Journal of Education, 2019)
This essay examines the work of Maria Zambrano, with particular reference to the connection between philosophy and life, between self-writing and the construction of the person. In our opinion, Zambrano's reflection about the writing symbolically embodies many of the antinomies underlying each process of education and self-formation. This dialectic of exile and permanence vividly expresses the essence of building oneself, of losing oneself and finding oneself. The confession is presented, therefore, as a form of writing and knowledge characterized by its peculiar ambivalent nature, contradictory but also mediating, in the name of a double movement of escape from oneself, on the one hand, and of seeking a center of one's inner universe on the other. According to Zambrano, there is a profound connection between the condition of exile, that of writing and that of a regained citizenship, if not a real homeland. This figure of Zambrano's thought is reflected and embodied, in an emblematic way, in the act of writing. Through writing this condition of exile becomes not only more wound, loss, abandonment and trauma, but the form of a radical experience of thought.